[Rezension von: Robert Ashmore, The transport of reading, text and understanding in the world of Tao Qian (365-427)]: book reviews-China - Wagner, Rudolf G. (The journal of Asian studies, 2014)
//static.cambridge.org/content/id/urn%3Acambridge.org%3Aid%3Aarticle%3AS0021911813001885/resource/name/firstPage-S0021911813001885a.jpg